Relationship between Medication Adherence and the Glycemic Control in Type 2 Diabetic Patients in Sulaimaniyah City, Kurdistan Region, Iraq - Khdir, Derin Ahmed; Mohammed, Mohammed Omer (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Type 2 diabetes mellitus (T2DM) implies the highest incidence of diabetic cases. T2DM is related to metabolic ailments in the pancreas, kidneys, liver, and intestines. Objective: To determine the impact of adherence to antidiabetic medication (ADMs) on glycemic control in T2DM patients. Methods: This quasi-experimental study enrolled 245 participants (119 intervention patients and 126 non-intervention patients) with T2DM in the Diabetes and Endocrine Center, Sulaimaniyah, Iraq, from January to August 2021. ADMs used the Morisky Medication Adherence Scale Item 8 (MMAS-8). Also, fasting blood glucose (FBG) and glycosylated hemoglobin (HbA1c %) were checked to assess glycemic control among the participants. Results: The counseling program potentially improved ADMs as the rate of medium adherence increased significantly from 5.0% to 31.9% (p<0.001), with a significant improvement in glycemic control in the intervention group from 13.9% (before the intervention) to 21.8% (after the intervention) (p=0.039). However, there was no significant difference between ADMs and glycemic control (p>0.999). Conclusion: Patients’ education and medication counseling significantly improved ADMs and glycemic control in people with T2DM.
Keywords: Diabetes mellitus; medication adherence; glycemic control; patients counselling